2022
DOI: 10.1002/anie.202217071
|View full text |Cite
|
Sign up to set email alerts
|

Iron Nanoparticles Protected by Chainmail‐structured Graphene for Durable Electrocatalytic Nitrate Reduction to Nitrogen

Abstract: The electrochemical nitrate reduction reaction (NO 3 RR) is an appealing technology for regulating the nitrogen cycle. Metallic iron is one of the well-known electrocatalysts for NO 3 RR, but it suffers from poor durability due to leaching and oxidation of iron during the electrocatalytic process. In this work, a graphenenanochainmail-protected iron nanoparticle (Fe@Gnc) electrocatalyst is reported. It displays superior nitrate removal efficiency and high nitrogen selectivity. Notably, the catalyst delivers ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 63 publications
0
56
0
Order By: Relevance
“…[39][40][41] 3d transition metal anchoring plays a significant contribution in improving the electronic structure and electrical conductivity of gÀ C 3 N 4 , which is mainly manifested in that the charge redistribution between metal and two-dimensional material can effectively regulate the catalytic performance, and has been widely used in the field of electrocatalysis. [42][43][44][45][46] In addition, the study found that the organic ligand modification can effectively optimize the adsorption of 3d-metal (hydro)oxides and metal oxyhydroxides with intermediates, thus improving the catalytic activity. [47,48] Therefore, the smart electrocatalytic materials were designed and constructed with 3d metal anchored gÀ C 3 N 4 as the carrier and amphoteric conjugate ligand as pH sensing modification phase.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[39][40][41] 3d transition metal anchoring plays a significant contribution in improving the electronic structure and electrical conductivity of gÀ C 3 N 4 , which is mainly manifested in that the charge redistribution between metal and two-dimensional material can effectively regulate the catalytic performance, and has been widely used in the field of electrocatalysis. [42][43][44][45][46] In addition, the study found that the organic ligand modification can effectively optimize the adsorption of 3d-metal (hydro)oxides and metal oxyhydroxides with intermediates, thus improving the catalytic activity. [47,48] Therefore, the smart electrocatalytic materials were designed and constructed with 3d metal anchored gÀ C 3 N 4 as the carrier and amphoteric conjugate ligand as pH sensing modification phase.…”
Section: Introductionmentioning
confidence: 97%
“…The pyridinic‐N in the heptazine hetero‐rings apt to withdraw electrons, providing abundant lone electron pairs for trapping metal ions, achieving homogeneity of metal anchoring and providing accurate information for active site identification [39–41] . 3d transition metal anchoring plays a significant contribution in improving the electronic structure and electrical conductivity of g−C 3 N 4 , which is mainly manifested in that the charge redistribution between metal and two‐dimensional material can effectively regulate the catalytic performance, and has been widely used in the field of electrocatalysis [42–46] . In addition, the study found that the organic ligand modification can effectively optimize the adsorption of 3d‐metal (hydro)oxides and metal oxyhydroxides with intermediates, thus improving the catalytic activity [47,48] .…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia (NH 3 ), as an important commodity or energy carrier, is critical to chemical synthesis, fertilizer manufacturing, and renewable energy storage and conversion, greatly impacting the development of modern society. Current large-scale NH 3 synthesis still relies heavily on the energy- and capital-intensive Haber–Bosch process, which consumes 2% of the global energy and produces >1% of the global CO 2 emissions. , Recently, intensive efforts have been devoted to developing a sustainable and eco-friendly alternative for NH 3 production, and the electrochemical nitrogen reduction reaction (NRR) under mild conditions powered by renewable energy sources has attracted extensive attention. However, the selectivity and yield of NH 3 produced via the NRR are extremely low because of the low water solubility and high NN bond dissociation energy (945 kJ mol –1 ) of N 2 , which are far behind the industrial requirements. , The electroreduction of nitrate (NO 3 – ), which has a high water solubility and low NO bond dissociation energy (204 kJ mol –1 ), , has great potential to produce NH 3 at a faster reaction rate while eliminating NO 3 – pollution in the environment. Nevertheless, the NO 3 – reduction reaction (NO 3 RR) to NH 3 involves multiple electron and proton transfer processes, which may afford different products including NO 2 – , NO, N 2 , and NH 2 OH, and thus exhibits an unsatisfactory NH 3 selectivity. Therefore, developing a highly efficient and selective catalyst for the NO 3 RR to NH 3 is a prerequisite.…”
Section: Introductionmentioning
confidence: 99%
“…30 To solve these problems, various strategies have been developed to improve the stability of Fe-based catalysts. [31][32][33] Among them, the loading strategy is deemed energetically feasible. [34][35][36] However, it is still a challenge to obtain uniformly dispersed iron-based nanoparticles on support without agglomeration.…”
mentioning
confidence: 99%